Especiação, quantificação, distribuição e transporte de mercúrio em solos contaminados do município de Descoberto, Minas Gerais - Walter Alves Durao Junior (2010)
In 2002, the blooming of metallic mercury in an area of the soil of Descoberto was observed. Municipal and state health representatives, besides research centers, performed several actions to evaluate the situation and guarantee the populations safety. The obtained results for soil superficial layer indicated Hg concentrations above the level in which there is potential risk of damage to human health (12 mg kg-1). In the studied soil samples quantitative analysis were performed through the HGAAS and DMA techniques, as well as the speciation analysis of Hg using a TDAAS system and studies of chemical fractionation obtained through the HGAAS system. The means of extraction used were: deionized water, CH3COOH 0,1 mol L-1+ HCl 0,001 mol L-1, KOH 1 mol L-1, HNO3 12 mol L-1, HCl 6 mol L-1 e aqua regia. The assessment of total Hg in different granulometries indicated the importance of evaluating the thickest fraction, since the Hg is retained in relevant concentrations in it. The speciation studies showed that, despite the fact that thecontamination had been due to the Hg0, the oxidation occurs and samples with high Hg2+ concentrations (90 mg kg-1) can be found, practically all of it as the Hg2+. The statistical interpretation of the results of chemical fractionation, along with the results of physical and chemical characterization of the samples, showed that the mercury present in the soil of the site, due to gold mining activities in the period 1824 to midtwentieth century, exists in the environment in its little mobile form. This attests that this metal is oxidized and linked mainly to oxy-hydroxides of iron, manganese and aluminum. Part of the Hg is also linked to the humic fraction, reaching 30%. Studies on the use of the heat treatment as a procedure to determine the Hg0 showed that at 180 °C, for 48 hours, the heating of the metal promotes its reduction and subsequent volatilization. This study suggests that the methodology applied bymany authors to quantify the elemental mercury may be overestimating the amount of metal in this form. In the interconversion studies between the Hg0/Hg2+, it was observed that in the samples spiked with the Hg0, there was oxidation, and in the samples spiked with Hg2+, there was reduction. However, the Hg oxidation kinetics was faster than the Hgreduction kinetics. This may justify the great amount of metal in the oxidated form found in the samples